A incorporação das tecnologias de informação e comunicação na gestão das escolas brasileira - Pontes, Helena Nascimento da Silva Alves (2022)
This study analyzes the state of incorporation of Information and Communication Technologies (ICTs) in school management activities of Brazilian basic education. With this intention, the work seeks to describe the profile of school principals, ascertain the existence and frequency of intra-school discussions on the use of ICTs and the participation of the director in external decisions on acquisition of these technologies for school. In addition, we sought to point out in which dimensions of school management has been incorporated the use of ICTs and verify the level of use of electronic data, applications and social networks in school management activities.We used secondary data from the ICT Education 2020 survey, whose sample included 3678 managers of public and private schools in activity, located in urban and rural areas and offering Elementary and High School, in regular mode. In terms of methodology, the research is configured as quantitative, in which were selected metric and non-metric variables that responded to the objectives of the study in order to be dispersion and form, as by cross-table statistical techniques, chi-square test, correlation coefficient and t test for independent samples.With a predominance of female managers, the sample demonstrated recent and high use of the Internet, but reduced participation in training activities on the use of technologies and the Internet. A large part of the managers stated that they recently met with the school team to discuss the use of technologies in school, but a smaller number said they frequently participate in extra-school decision-making processes (in the school network) acquisition of ICTs for use in school. The sample presented the incorporation of information and communication, with more intensity, in school management activities that involve the dimensions of Communication Management, Administrative Management and Pedagogical Management, especially in the use of data in electronic format and use of social networks. There is a high degree of registration or consultation of data and information in electronic format in schools, especially when it refers to the registration data of students, usually required at the time of enrollment, as well as their frequency and grades, information whose registration assists in monitoring educational results, abandonment and dropout. Regarding the use of mobile phone or tablet applications in the management of schools, it was found that it is still low, probably because most of the schools surveyed declared not to have this type of software. In contrast, the level of activities of use of social networks in the management of schools behaved more elevated and balanced, highlighting among them the sending of messages and reports to students, parents and guardians through these digital tools. The analysis showed that recent participation in training on the use of technologies and the Internet contributed to a higher average of the use of electronic data, applications and social networks in the management and communication of schools.